PENERAPAN METODE KOOPERATIF TIPE PICTURE AND PICTURE MENGGUNAKAN MEDIA GAMBAR DALAM PEMBELAJARAN SEJARAH KELAS XI DI SMA N 1 KOTA JAMBI TA 2021-2022 - Purba, Rory Digashanda; Azmi, Ulul (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2022)
Research on the implementation of picture-assisted learning media cooperative learning in history learning class xi in SMA 1 Jambi city in each cycle on learning outcomes increased after using the cooperative learning method of picture-assisted learning media and pictures. The percentage of students' completeness in the first cycle is 60%, in the second cycle, the percentage of students' completeness learning outcomes is 90%, while in the third cycle the percentage of complete learning outcomes is 100%. This means that there is an increase from cycle I to cycle II and cycle III. While the percentage of completeness of student learning outcomes reached 100%. That is, dominantly students have obtained mastery learning. Therefore, it can be written in this conclusion that there is an increase in student learning outcomes in class XI history subjects using the Cooperative Method of Learning Type Picture And Picture Media Pictures in History Learning Class XI IN SMA N 1 Jambi City